Fabrication analysis of flat vacuum enclosures for solar collectors sealed with Cerasolzer 217. (15th May 2021) - Arya, Farid; Hyde, Trevor; Henshall, Paul; Eames, Philip; Moss, Roger; Shire, Stan; Uhomoibhi, James
Highlights: Vacuum Flat Plate Enclosures were fabricated involving Ultrasonic Soldering techniques. Tin-based alloy, Cerasolzer 217, used to create the vacuum seal. Mechanical structural analysis undertaken to study stresses. Digital Image Correlation (DIC) used to study the strain profile. Helium mass spectrometer leak detector used to investigate the hermeticity of edge seal. Abstract: Vacuum flat plate (VFP) solar thermal collectors exhibit excellent optical and thermal characteristics due to a combination of wide surface area and high vacuum thermal insulation offering a high performance and architecturally versatile collector with a variety of applications for industrial process heat and building integration. A vacuum flat plate solar collector consists of a solar absorber in a flat vacuum enclosure comprising glass or glass and metal covers sealed around the periphery with an array of support pillars to maintain the separation of the enclosure under atmospheric pressure. The edge seal must be both mechanically strong and hermetic to ensure the durability of the internal vacuum over collector lifetime. This presents several challenges for the fabrication of flat vacuum enclosures. In this study a novel sealing technique is presented using a tin-based alloy, Cerasolzer 217, to create the vacuum seal between two glass panes and an edge separating spacer. The sealing process is undertaken at temperatures ≤250 °C allowing the use of thermally tempered glass panes. The mechanical strength of the edge seal was investigated using a tensometer. It was demonstrated that the bond between glass and edge spacer was sufficiently strong to withstand induced stresses in the edge seal region. The edge seal was leak tested using a conventional Helium mass spectrometer leak detector and was shown to possess leak rates low enough to maintain an adequate vacuum pressure to supress conductive and convective heat transfer in the collector. A finite element method (FEM) is developed and validated against the experimental results and employed to predict the stresses in different regions of the enclosure. It was found that the mechanical strength limits of the seal and glass are higher than the stresses in the edge seal region and on the glass surface, respectively.